2020
DOI: 10.1093/rb/rbaa013
|View full text |Cite
|
Sign up to set email alerts
|

The optimized preparation of HA/L-TiO2/D-TiO2 composite coating on porous titanium and its effect on the behavior osteoblasts

Abstract: Various surface bioactivation technology has been confirmed to improve the osteogenic ability of porous titanium (pTi) implants effectively. In this study, a three-layered composite coating, i.e. outer layer of hydroxyapatite (HA), middle layer of loose titanium dioxide (L-TiO2) and inner layer of dense TiO2 (D-TiO2), was fabricated on pTi by a combined processing procedure of pickling, alkali heat (AH), anodic oxidation (AO), electrochemical deposition (ED) and hydrothermal treatment (HT). After soaking in si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…By changing the Acid etching or alkali-heat treatment parameters, such as immersion temperature, duration, acid or alkali concentration, and heating furnace temperature, the surface of different scales or morphologies can be formed (Zhuang et al, 2014;Kato et al, 2015;Fu et al, 2020). A common acid etching treatment is to soak the titanium-based implants in a strong acid solution for 60 min at 60-100 °C and ultrasonic vibration (Souza et al, 2019).…”
Section: Acid/alkali Treatment and Anodization Treatmentmentioning
confidence: 99%
“…By changing the Acid etching or alkali-heat treatment parameters, such as immersion temperature, duration, acid or alkali concentration, and heating furnace temperature, the surface of different scales or morphologies can be formed (Zhuang et al, 2014;Kato et al, 2015;Fu et al, 2020). A common acid etching treatment is to soak the titanium-based implants in a strong acid solution for 60 min at 60-100 °C and ultrasonic vibration (Souza et al, 2019).…”
Section: Acid/alkali Treatment and Anodization Treatmentmentioning
confidence: 99%
“…It has been found that materials with a combination of micro-and nanostructured surfaces with a certain roughness can show improved levels of cell attachment [13]. Methods such as sandblasting and acid etching [14,15], anodic oxidation [16], plasma spraying [17], magnetron sputtering [18], or meniscus-dragging deposition [19] are commonly used for surface modification. These methods assume contact with the material, so they have some limitations to their universal use such as limitations in substrate size or contamination with hazardous chemicals [20].…”
Section: Introductionmentioning
confidence: 99%
“…In this way, various strategies have been created to stimulate the antibacterial properties of TiO 2 scaffolds in the presence of PLGA [ 28 ]. Among other things, the osteogenic ability of Ti has been studied to assess the effects of osteoblastic activity on this material [ 29 ]. Likewise, the analysis of the surface of Ti compounds to improve the contact of biomaterials has been evaluated by means of techniques, such as plasma and anodic oxidation [ 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ].…”
Section: Introductionmentioning
confidence: 99%